2015
DOI: 10.1039/c4an01731e
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative serine protease assays based on formation of copper(ii)–oligopeptide complexes

Abstract: A quantitative protease assay based on the formation of a copper-oligopeptide complex is developed. In this assay, when a tripeptide GGH fragment is cleaved from an oligopeptide chain by serine proteases, the tripeptide quickly forms a pink GGH/Cu(2+) complex whose concentration can be determined quantitatively by using UV-Vis spectroscopy. Therefore, activities of serine proteases can be determined from the formation rate of the GGH/Cu(2+) complex. This principle can be used to detect the presence of serine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…For example, amino terminal copper and nickel (ATCUN)-binding peptide with a structural characterization comprising of a free NH 2 -terminus, a histidine (His) residue in the third position and two intervening peptide nitrogens (denoted as NH 2 -X-X-His sequence) exhibits high affinity to Cu 2+ ion. [37][38][39][40] The formation of ATCUN-Cu 2+ complex depresses Cu 2+ -initiated redox cycling for AA oxidation. 40 In this work, we demonstrated that the PSA substrate peptide (DAHSSKLQLAPP) that contains an ATCUN motif of DAH can sequestrate Cu 2+ by the formation of ATCUN-Cu 2+ complex ( Figure 1A), thus depressing the Cu 2+ -catalyzed oxidation of AA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, amino terminal copper and nickel (ATCUN)-binding peptide with a structural characterization comprising of a free NH 2 -terminus, a histidine (His) residue in the third position and two intervening peptide nitrogens (denoted as NH 2 -X-X-His sequence) exhibits high affinity to Cu 2+ ion. [37][38][39][40] The formation of ATCUN-Cu 2+ complex depresses Cu 2+ -initiated redox cycling for AA oxidation. 40 In this work, we demonstrated that the PSA substrate peptide (DAHSSKLQLAPP) that contains an ATCUN motif of DAH can sequestrate Cu 2+ by the formation of ATCUN-Cu 2+ complex ( Figure 1A), thus depressing the Cu 2+ -catalyzed oxidation of AA.…”
Section: Introductionmentioning
confidence: 99%
“…MTS reagents are a reasonable choice to suppress irreversible denaturation of globular proteins triggered by disulphide bond breakage due to their high thiol-specificity and rapid protection ability. Traditionally, copper(II) ions were used as an effective suppressor of disulphide-thiol exchange protein denaturation 14 , 15 , but copper(II) catalyses unfavourable methionine oxidation, and the formation of copper(II) hydroxide precipitates often interferes with optical analysis 29 . Thiol-specific irreversible blockers, such as NEM and IAA, protect thiols generated by breakage of disulphide bonds upon heating by S -alkylation.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the methods described here were not originally designed to screen the activity of viral proteases in the presence of inhibitors, they can be adapted for this purpose by simply changing the peptide sequence to the target site of the protease of interest. The cleavage yield is usually monitored either colorimetrically (Ding and Yang, 2015;Zhou et al, 2014) or as a change in fluorescence triggered by the release of fluorescent labels such as 7-amido-4-methylcoumarin (AMC) or rhodamine (Grant et al, 2002). Fluorogenic substrates have been used to determine the activity of coronavirus proteases and screen inhibitors (Kuo et al, 2004;Lee et al, 2014;Park et al, 2017;Song et al, 2014;Tomar et al, 2015;Wang et al, 2016;Yang et al, 2005;Zhao et al, 2008).…”
Section: Assay and Methods For Screening And Evaluating Viral Maturatmentioning
confidence: 99%